Construct and Criterion Validation of Social Phobia Inventory Indonesian Version - Alfina Rizkia; Samsunuwiyati Mar'at; Fr. Tommy Y. S. Suyasa (Journal La Sociale, 2024)
Social anxiety disorder or SAD is a condition of abnormal anxiety experienced by individuals when they are facing a social situation. People with SAD usually tend to avoid social situations because they are afraid or anxious of getting a negative evaluation from other people. The negative impact for people with SAD is important for the need for measuring instruments that can detect the symptoms. The lack of SAD measurement tools in Indonesia is the reason why this validation study (SPIN) is important. The Social Phobia Inventory or SPIN is a self-report measurement tool for SAD symptoms and has good both in reliability and validity in several countries. This study aims to prove the validity and reliability of SPIN in Indonesia with 118 participants. The participants include people with SAD and healthy people. The result of this study that they are a convergent validity between SPIN and Social Cognition Questionnaire (SCQ), discriminant validity between SPIN and Patient Health Questionnaire (PHQ) that evaluate eating disorder and alcohol abuse symptoms, and also SPIN have 66% of sensitivity and 100% of specificity using Liebowitz Social Anxiety Scale (LSAS). This study can be used by professionals to assist in determining an objective diagnosis in individuals with symptoms of SAD using SPIN since SPIN is one of the gold standard to measure social anxiety symptoms.